The use of recovery strategies in professional soccer: a worldwide survey - Dahl, E. B.; Øygard, E.; Paulsen, G.; Rud, B.; Losnegard, T. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Preconditioning exercise is a widely used strategy believed to enhance performance later the same day. The authors examined the influence of preconditioning exercises 6 hours prior to a time-to-exhaustion (TTE) test during treadmill running.